Potensi Predator Coccinella Transversalis Fabricius (Coleoptera: Coccinellidae) sebagai Agen Hayati Pengendali Hama Thrips Parvispinus Karny (Thysanoptera: Thripidae) pada Tanaman Cabai Besar (Capsicum Annuum L.) - NI KETUT JULI DWI JAYANTI; KETUT AYU YULIADHI; I NYOMAN WIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
The Potential of Predator Coccinella transversalis Fabricius (Coleoptera: Coccinellidae) as A Biology Control Agent Thrips parvispinus Karny (Thysanoptera: Thripidae) in Chili Plant (Capsicum annuum L.)Thrips parvispinus Karny (Thysanoptera: Thripidae) is one of the main pests in the cultivation of chili. T. parvispinus existence can damage chili plants and decrease production. This study aims to determine the potential of predator Coccinella transversalis required predation testing which includes a value of searching time (a), handling time (Th) and functional response C. transversalis to T. parvispinus on chili plants. The prey densities presented were 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 and 22 individuals. The exposure is done for twelve hours. Predator C. transversalis used is a female imago that has been fasted for 24 hours. The determination of functional response type was analyzed by regression analysis, while the predation rate is analyzed using Holling formula. The results showed that the prey density affects the predation rate and the functional response type C. Transversalis. The rate of C. transversalis predation is significantly different in each number of prey exposed. Similarly, on the basis of regression analysis, it is shown that C. transversalis has a functional response of type I to T. parvispinus prey. These results indicate that C. transversalis has potential as a biological control agent.